Influencing factors and improvement methods of coronary artery plaque evaluation in CT - Gao, Yaqi; Pan, Yao; Jia, Chongfu (Frontiers in Cardiovascular Medicine, 2024)
Accurate evaluation of the nature and composition of coronary plaque involves clinical follow-up and prognosis. Coronary CT angiography is the most commonly non-invasive method for plaque evaluation, however, the qualitative and quantitative evaluation of plaque based on CT value is inaccurate, due to the influence of luminal attenuation, tube voltage, parameter setting and the subjectivity.